Optimal Location And Size of The STATCOM to Enhance The Power System Stability - Mohamad A. Khalaf; Abdulsatar H. Jasim; Bilal A. Nasir (NTU Journal of Engineering and Technology)
The importance of power system operation is becoming increasingly significant due to the escalating demand observed in many nations. The exponential growth in load demand exerts substantial stress on electrical power systems, since they run in close proximity to their critical thresholds due to limitations imposed by environmental and economic factors. The basic goal of operating electrical power networks is to efficiently supply energy to users at optimal frequency and voltage levels, with a focus on cost minimization.